Assessing the rise of organic farming in the European Union: Environmental and socioeconomic consequences - Charalampos Konstantinidis (University of Massachusetts, Department of Economics, 2012)
Although organic farming is considered the poster child of rural development in Europe, there is little empirical evidence assessing its success in achieving the ambitious environmental and socio-economic objectives that it is purported to assist. This paper presents empirical evidence from the growth of organic farming in Europe over the past two decades that questions the highly optimistic claims of policy makers. Although policies in support of organic impact have had an overall positive environmental impact, their social impact is ambiguous, as organic farming appears to have grown more in areas with larger average farm sizes. Additionally, contrary to what is often assumed, organic farms in Europe display larger average sizes and lower rates of labor intensity than their conventional counterparts, casting doubts on the efficacy of organic farms to allow family farmers to remain in the countryside as high-value producers. I assert that this this development should be viewed as evidence of the conventionalization of organic farming, and suggest that policy makers take into account the transformations of the structures of production, which benefit from the support for organic farming. Treating the experience of organic farmers in the EU as a lesson for schemes paying for environmental services, I suggest that the success of organic farming should be evaluated by the numbers of participating farmers, rather than by area covered, as has been the predominant approach so far. Finally, I assert that strong agricultural cooperatives are necessary to secure a long-lasting passage of small farmers to organic methods of production.
Keywords: Q1; Q58; O52; 330